2015
DOI: 10.3233/jrs-150707
|View full text |Cite
|
Sign up to set email alerts
|

Effects of balance training on post-sprained ankle joint instability

Abstract: Balance training is an effective training method for rehabilitation of instable ankle. Different approaches to balance training provide in general similar improvement for sprained ankle.Implications for future studies:More RCTs on chronic ankle instability are needed with large sample size and use of different intensities of exercises. It would be better for the UB FAU to provide access to articles so that students and researches could download articles for free from different electronic sources.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Although there was no speci c proprioceptive exercise intervention, improvements in stability are similar to those found after implementing various approaches to balance training [17].…”
Section: Stabilitymentioning
confidence: 56%
See 2 more Smart Citations
“…Although there was no speci c proprioceptive exercise intervention, improvements in stability are similar to those found after implementing various approaches to balance training [17].…”
Section: Stabilitymentioning
confidence: 56%
“…Ankle sprains represent in soccer practice one of the injuries leading to the greatest loss of training time. To reduce the risk of injury in an unstable ankle, as a result of restricted range of motion or poor stability, balance should be improved [17], attempting to reduce perceived pain by increasing strength [18].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As both PT and BT play a role in improving postural control and stability [13,33,41], it would have been improved in all hop tests in this study as well. Although both groups showed improved results in all hop tests, the interaction effect in the triple hop was perhaps due to the effect of core stability training, which is the main focus of PT.…”
Section: Discussionmentioning
confidence: 96%
“…In previous studies, several authors have reported that BT affects balance and also improves ankle strength [13,33]. BT stimulates the muscle fibers and nerves around the ankle during static and dynamic postural control in a closed kinetic In addition, it has been reported that the balance equipment used to provide perturbation affects activation of the ankle muscles, such as the tibialis anterior, peroneus longus, and medial gastrocnemius [34].…”
Section: Discussionmentioning
confidence: 99%